Integration of Rough Cut Capacity Planning (RCCP) and Capacity Constraint Resources (CCR) to Minimize the Risk of Uncertainty in Fulfilling Production Material Supply - Salsavira, Nardha Livia; Yuliawati, Evi; Rahmawati, Nur; Trihastuti, Dian (Widya Teknik, 2023)
Managing the production capability of a company is undoubtedly the main concentration in the manufacturing industry. Industries must consider the materials and resources supplied for making a master production schedule. The lack of material supply from a supplier results in the inefficiency of the production process. The supply disruption of raw materials results in problems for the rest of the stages in the production process. As a result, companies experience difficulties in meeting the predetermined target. This research used an integration of RCCP and CCR to solve the problem. Optimization of CCR implies the TOC (theory of constraint) principle by reducing the percentage of overload until reaching a balanced (optimal) condition. This research aims to balance and optimize the ongoing production process. It took place in a manufacturing company that produces building materials serving the market in Indonesia. The results show that during the observation period, the current production system has experienced system overload for about 70% of the production period. The results of the RCCP analysis provide recommendations for improving the master production schedule to increase the effectiveness of the production system.